2010
DOI: 10.2169/internalmedicine.49.3258
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese Case of Fragile-X-Associated Tremor/ataxia Syndrome (FXTAS)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Until recently FXTAS was defined as a late-onset neurodegenerative disorder, but evidence from animal models and from observations of children with elevated levels of FMR1 mRNA showing developmental delay, behaviour difficulties and increased seizure activity, suggest that the underlying pathogenic process may begin at or before birth [ 34 ]. Neuroimaging studies of affected individuals show global loss of brain volume, in particular cerebellar and cortical atrophy and hyperintensity white matter lesions around the periventricular area and in the middle cerebellar peduncles [ 35 ].…”
Section: Clinical and Molecular Descriptionmentioning
confidence: 99%
“…Until recently FXTAS was defined as a late-onset neurodegenerative disorder, but evidence from animal models and from observations of children with elevated levels of FMR1 mRNA showing developmental delay, behaviour difficulties and increased seizure activity, suggest that the underlying pathogenic process may begin at or before birth [ 34 ]. Neuroimaging studies of affected individuals show global loss of brain volume, in particular cerebellar and cortical atrophy and hyperintensity white matter lesions around the periventricular area and in the middle cerebellar peduncles [ 35 ].…”
Section: Clinical and Molecular Descriptionmentioning
confidence: 99%
“…The exact reason for this is currently unknown. Recently, Ishii et al [12] reported the first Japanese FXTAS patient who was initially diagnosed with essential tremor. Recognizing FXTAS patients with predominant cognitive impairment would contribute to our understanding of the disease's phenotypic variation.…”
Section: Discussionmentioning
confidence: 99%
“…The syndrome can mimic many common neurodegenerative disorders such as Parkinson's disease (PD),multiple system atrophy (MSA), Alzheimer disorders (AD), essential tremor (ET), and pure ataxia. Tremor is seen in 48-80% patients and variable in different studies and intention tremor is the most common pattern [1,2]. But it's very rare that FXTAS patients present with orthostatic tremor (OT).…”
Section: Introductionmentioning
confidence: 99%